2014
DOI: 10.1007/s00438-014-0957-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of root morphological traits in wheat

Abstract: Traits related to root architecture are of great importance for yield performance of crop species, although they remain poorly understood. The present study is aimed at identifying the genomic regions involved in the control of root morphological traits in durum wheat (Triticum durum Desf.). A set of 123 recombinant inbred lines derived from the durum wheat cross of cvs. 'Creso' × 'Pedroso' were grown hydroponically to two growth stages, and were phenotypically evaluated for a number of root traits. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 97 publications
4
20
0
Order By: Relevance
“…The QTL on the short arm of chromosome 7B is of particular interest, whereby it is involved in the control of root length, volume, and surface area, but only for the largest root-diameter class. Similarly, in a previous study, a QTL that controlled root length, volume, and surface area only in a specific root-diameter class was identified in the “Creso” × “Pedroso” segregating population [ 67 ]. This finding indicates that specific loci can act in shaping the morphology of the root apparatus only in particular growth phases.…”
Section: Discussionmentioning
confidence: 58%
“…The QTL on the short arm of chromosome 7B is of particular interest, whereby it is involved in the control of root length, volume, and surface area, but only for the largest root-diameter class. Similarly, in a previous study, a QTL that controlled root length, volume, and surface area only in a specific root-diameter class was identified in the “Creso” × “Pedroso” segregating population [ 67 ]. This finding indicates that specific loci can act in shaping the morphology of the root apparatus only in particular growth phases.…”
Section: Discussionmentioning
confidence: 58%
“…Several wheat studies have evaluated roots using different phenotyping methods including rhizotrons (Nagel et al, 2012;Lobet and Draye, 2013;Clarke et al, 2017), soil coring (Trachsel et al, 2011;Wasson et al, 2012;Wasson et al, 2014), lysimeters (Ehdaie et al, 2014;Elazab et al, 2016), hydroponics (Liu et al, 2015), paper roll culture and Petri dishes for seedling (Tomar et al, 2016), rhizoboxes (Fang et al, 2017, and X-ray-computed tomography (Gregory et al, 2003;Mairhofer et al, 2013;Colombi and Walter, 2017;Flavel et al, 2017). This has encouraged researchers to develop high-throughput strategies that focus on key proxy traits linked to root system architecture displayed in the field (Petrarulo et al, 2015;Richard et al, 2015). This has encouraged researchers to develop high-throughput strategies that focus on key proxy traits linked to root system architecture displayed in the field (Petrarulo et al, 2015;Richard et al, 2015).…”
Section: Root System Architecture and Its Association With Yield Undementioning
confidence: 99%
“…However, most of these techniques are either expensive or not precise enough and reproducible. This has encouraged researchers to develop high-throughput strategies that focus on key proxy traits linked to root system architecture displayed in the field (Petrarulo et al, 2015;Richard et al, 2015). One such example is the "clear pot" method first developed by Richard et al (2015) in hexaploid wheat, and later adapted to barley (Hordeum vulgare L.; Robinson et al, 2016).…”
mentioning
confidence: 99%
“…however, the environment of root development in this [32]. The GWAS results also showed that some SNP loci that control multiple root traits were detected under all three cultivation patterns or at all stages except the MS.…”
Section: Effects Of Different Cultivation Patterns On Wheat Root Devementioning
confidence: 52%